Perioperative Management of Elective Surgery in Patients with COVID-19 Infection - Tjokorda Gde Agung Senapathi; I Made Gede Widnyana; Marilaeta Cindryani; Win Muliadi; Madyline Victorya Katipana (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif (PERDATIN) / The Indonesian Society of Anesthesiology and Intensive Care (INSAIC), 2023)
SARS-CoV2 is a deadly virus belonging to the family Corona-viridae, with the primary target pulmonary system, known as the coronavirus pandemic disease (COVID-19). This virus has caused a high death rate of approximately 9,500 deaths as of December 2020. Along this pandemic, the hospital will treat non-emergent conditions in COVID-19 patients require nonemergent surgery. Anesthesiologists have an important role in the anesthesia management in patients with COVID-19 utilization and require airway management. This article explains optimal preoperative evaluation, intraoperative management, and postoperative management of COVID-19 patients. Optimal treatment is expected to minimize complications and the spread of COVID-19 disease. The optimal time for elective surgery should be decided by a multidisciplinary committee that considers the risk of complications either the patient, the disease itself, the surgical procedure, or other alternatives with lower risk. Perioperative management is carried out preoperatively, intraoperatively, and postoperatively. The safety of anesthesiologists using personal protective equipment (PPE) to carry out preoperative evaluations is important. The number of disease severity can use a scoring system, the results of which can be used as a reference for multidisciplinary discussions related to perioperative management plans. General anesthesia can contribute to the spread of disease resulting from the risk of droplets resulting from airway action, so regional anesthesia can be considered to reduce the risk of spread. For this reason, optimal management is needed to reduce risks to patients as well as medical personnel.